PENERAPAN BLUE ECONOMY PADA PENGEMBANGAN PARIWISATA BERKELANJUTAN DI KAWASAN PESISIR BALI UTARA, SINGARAJA: PENERAPAN BLUE ECONOMY PADA PENGEMBANGAN PARIWISATA BERKELANJUTAN DI KAWASAN PESISIR BALI UTARA, SINGARAJA - I Kadek Donny Wishanesta; I Gede Putra Perdana; Putu Rana Janendra (Universitas Udayana, 2025)
The research is titled “The Application of the Blue economy in the Development of Sustainable Tourism in the Northern Bali Coastal Area, Singaraja.” This is a qualitative study aimed at understanding the development of Blue economy-based economic activities in the Northern Bali Coastal Area, Singaraja, as well as identifying the developments that have been carried out by the government, particularly in the fields of tourism and fisheries, and assessing the economic, social, and environmental impacts. This study employs a descriptive qualitative method, with data collection techniques including open-ended and in-depth interviews, field observations, and documentation. Data analysis involves data reduction, data presentation, and drawing conclusions/verification. The results of the study on the development of Blue economy-based economic activities in the North Bali Coastal Area, Singaraja. The economic development carried out by the government, particularly in the tourism sector, has been implemented through various activities such as the construction of a toll road (shortcut) to Singaraja, hotels and accommodations as supporting infrastructure, and the empowerment of communities and business owners. In the process of implementing these government projects, there have been impacts on the surrounding community, particularly in reducing unemployment rates, increasing community income, expanding business and employment opportunities, and promoting growth and development in other sectors. However, in terms of environmental aspects, the construction of infrastructure and projects has caused the community to feel disadvantaged due to inadequate environmental anticipation and control measures.